Engaging multiple weighting approaches and Conjoint Analysis to extend results acceptance of life cycle assessment in biological wastewater treatment technologies. (October 2018) - Bai, Shunwen; Zhao, Xinyue; Wang, Dawei; Zhang, Xuedong; Ren, Nanqi
Graphical abstract: Highlights: LCA evaluation for biological wastewater treatment technologies. Extend the explanatory ranges of LCA results using multiple weighting approaches. Derive appropriate strategies by coordinating the multiple weighting methods. Promote stakeholder's participation using Conjoint Analysis. Demonstrate the decision-making process of stakeholders by Conjoint Analysis. Abstract: Environmental impacts of biological wastewater treatment technologies (BWTTs) can be evaluated by life cycle assessment (LCA). However, very few efforts have been made to expand the ranges of results acceptance and promote stakeholders to participate in the results analysis. To facilitate the evaluation reaching more wide and deep understanding, this study proposed to employ multiple weighting methods and the Conjoint Analysis. To investigate the feasibility, an illustrative case of a bioaugmented constructed wetland was carried out. Weighting results indicated that appropriate improvement strategies could be obtained from synthesizing the similarities and differences of LCA results due to different weighting methods employed. Meanwhile, application of Conjoint Analysis was conducive to the communication between LCA practitioners and BWTTs stakeholders. In a simulated decision-situation, this study found that the decision-making process of stakeholders could be clearly derived to indicate how stakeholders would take trade-offs and make choices based on analyzing LCA outcome.